Alterations in gut microbiota of hyperthyroidism rats and the therapeutic effects of Radix Scrophulariae: A study based on fecal metabolomics and 16S rRNA gene sequencing analysis - Ning Zhang; Shumin Liu; Zihui Li; Xu Lu; Tao Ye (Heliyon)
Background: Radix Scrophulariae is traditionally used for its yin-nourishing and fire-reducing properties to treat hyperthyroidism caused by yin deficiency and excessive fire. The gut microbiota's interaction with the host endocrine system is thought to play a key role in its therapeutic effects, although the specific mechanisms remain unclear. Objective: This study aimed to determine whether the preventive and therapeutic effects of Radix Scrophulariae on hyperthyroidism are mediated through modulation of gut microbiota composition and fecal metabolites involved in hyperthyroidism pathogenesis. Methods: Hyperthyroid rats were treated with Radix Scrophulariae. Gut microbiota diversity was analyzed via 16S rRNA gene sequencing, and fecal metabolites were profiled using ultra-high-performance liquid chromatography coupled with time-of-flight mass spectrometry (UPLC-TOF-MS). KEGG pathway analysis identified affected metabolic pathways, and Pearson correlation analysis explored the associations between microbial genera and specific metabolites. Results: Radix Scrophulariae significantly restored 41 metabolites in hyperthyroid rats compared to the model group. These metabolites were involved in linoleic acid metabolism, sphingolipid metabolism, unsaturated fatty acid biosynthesis, primary bile acid biosynthesis, purine metabolism, and steroid hormone biosynthesis. Gut microbiota analysis revealed significant downregulation of Crenarchaeota (P ≤ 0.05) and modulation of 13 microbial genera, including five upregulated and four downregulated genera. These microorganisms were associated with key biological processes, such as membrane transport, carbohydrate metabolism, and amino acid metabolism. Conclusion: Radix Scrophulariae may exert therapeutic effects on hyperthyroidism by regulating gut microbiota and fecal metabolites, particularly through modulation of bile acid pathways and key microbial genera. These findings provide a mechanistic basis for its yin-nourishing and fire-reducing effects, offering insights into its potential for hyperthyroidism prevention and treatment.